Structural and Functional Characterization of the FadR Regulatory Protein from Vibrio alginolyticus - Gao, Rongsui; Li, Defeng; Lin, Yuan; Lin, Jingxia; Xia, Xiaoyun; Wang, Hui; Bi, Lijun; Zhu, Jun; Hassan, Bachar; Wang, Shihua; Feng, Youjun (Frontiers in Cellular and Infection Microbiology, 2017)
The structure of Vibrio cholerae FadR (VcFadR) complexed with the ligand oleoyl-CoA suggests an additional ligand-binding site. However, the fatty acid metabolism and its regulation is poorly addressed in Vibrio alginolyticus, a species closely-related to V. cholerae. Here, we show crystal structures of V. alginolyticus FadR (ValFadR) alone and its complex with the palmitoyl-CoA, a long-chain fatty acyl ligand different from the oleoyl-CoA occupied by VcFadR. Structural comparison indicates that both VcFadR and ValFadR consistently have an additional ligand-binding site (called site 2), which leads to more dramatic conformational-change of DNA-binding domain than that of the E. coli FadR (EcFadR). Isothermal titration calorimetry (ITC) analyses defines that the ligand-binding pattern of ValFadR (2:1) is distinct from that of EcFadR (1:1). Together with surface plasmon resonance (SPR), electrophoresis mobility shift assay (EMSA) demonstrates that ValFadR binds fabA, an important gene of unsaturated fatty acid (UFA) synthesis. The removal of fadR from V. cholerae attenuates fabA transcription and results in the unbalance of UFA/SFA incorporated into membrane phospholipids. Genetic complementation of the mutant version of fadR (Δ42, 136-177) lacking site 2 cannot restore the defective phenotypes of ΔfadR while the wild-type fadR gene and addition of exogenous oleate can restore them. Mice experiments reveals that VcFadR and its site 2 have roles in bacterial colonizing. Together, the results might represent an additional example that illustrates the Vibrio FadR-mediated lipid regulation and its role in pathogenesis.